From adversity to reflection: the resilient behavior of multidisciplinary health professionals. - Minello, Italo Fernando; Birrer, Jucelaine Arend (Revista de Administração da UFSM, 2012)
http://dx.doi.org/10.5902/198346595654 This article is based on exploratory type qualitative research, which has as objective to analyze the resilient behavior of multidisciplinary health professionals facing professional activities adversities. Eight interviews were profoundly conducted and analyzed by the technique of content analysis. Four categories of analysis were brought up (defined as non-priori): alliance or external support, professional identity, occupational stress and resilient behavior. The results showed the existence of stress in relation to the managing of activities, the motivation to continue in the program (which is its belief in the pedagogical proposal), and the external support (representing support to professional performance).